2011
DOI: 10.1261/rna.2759911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of syn nucleobases in the active sites of functional RNAs

Abstract: Biological RNAs, like their DNA counterparts, contain helical stretches, which have standard Watson-Crick base pairs in the anti conformation. Most functional RNAs also adopt geometries with far greater complexity such as bulges, loops, and multihelical junctions. Occasionally, nucleobases in these regions populate the syn conformation wherein the base resides close to or over the ribose sugar, which leads to a more compact state. The importance of the syn conformation to RNA function is largely unknown. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 73 publications
7
77
0
Order By: Relevance
“…Taken together, we show that RNA sequences which are bound by the RRM domain are enriched for specific dinucleotides possessing unique RNA conformation. While as expected from the chemical nature of RNA nucleotides we noticed a preference for dinucleotides containing G in syn conformation 44,32 and U in C2' endo conformation, we show that the RNA conformations were non-randomly distributed between all G and U containing dinucleotides, possibly providing an additional recognition code for RNA recognition by the RRM protein family.…”
Section: Enrichment Of Specific Dinucleotides In Rrm Binding Sequencessupporting
confidence: 73%
See 2 more Smart Citations
“…Taken together, we show that RNA sequences which are bound by the RRM domain are enriched for specific dinucleotides possessing unique RNA conformation. While as expected from the chemical nature of RNA nucleotides we noticed a preference for dinucleotides containing G in syn conformation 44,32 and U in C2' endo conformation, we show that the RNA conformations were non-randomly distributed between all G and U containing dinucleotides, possibly providing an additional recognition code for RNA recognition by the RRM protein family.…”
Section: Enrichment Of Specific Dinucleotides In Rrm Binding Sequencessupporting
confidence: 73%
“…44 This is also in agreement with a previous study that showed a preference for purines among syn nucleobases in functional RNAs. 32 We also noticed that the C2' endo conformation, which was most significant in the RRM binding interfaces, was preferably found in U nucleotides (Table S1). It has been previously shown that the C2' endo unusual sugar pucker conformation provides less steric hindrance compared with the more common conformation C3' endo.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…A10 is in a syn-conformation with a C2′-endo sugar pucker. It is possible that a correlation of A10 being in the syn-conformation changes the sugar pucker and thereby changes the A10 phosphate (scissile phosphate) to A11 phosphate distance for appropriate self-cleavage (26). This distance is longer than most other phosphate-phosphate distances (6.8 Å).…”
Section: Discussionmentioning
confidence: 99%
“…A10 may then be acting to aid for in-line nucleophilic attack. Hammerhead, HDV, glmS, and hairpin ribozymes all have nucleotides in syn-conformation at critical positions around their active site structures (26).…”
Section: Discussionmentioning
confidence: 99%